RESTITUSI BAGI ANAK KORBAN PENYALAHGUNAAN NARKOTIKA - Ika Dewi Sartika Saimima; Fransiska Novita Eleanora (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
ABSTRACT Children are trustworthy and entrusted by God Almighty, so they need to be given protection, and guarded and cared for to maturity, guarded and cared for in the sense of being given protection against themselves both protection from their parents, or others who are obliged to look after it or also from society, so as not to become a victim of the abuse of the narcotics. Narcotics itself is defined as a substance or drug that comes from plants or not from plants, whether it is also synthesis or not that harms anyone and if consumed in excessive amounts can cause death. If the child as a victim of abuse of narcotics resulting from mistreatment by ordering or forcing the child to consume it, is a violation of the child's rights, which will have an impact that the child is increasingly addicted to get these items, as well as efforts to escape from depression and stress, but with inviting children or involving or also telling children to consume them is unlawful, and includes damaging their lives. Protection of children is not only limited to providing drugs, and health services but also to get restitution as stipulated in Government Regulation Number 43 Year 2017 Regarding Provision of Restitution for child victims of crime, giving restitution to children because the effect of the child as a victim greatly affects the physical and psychic to grow and develop children. Research Method, this study uses normative juridical by referring to existing laws, concepts and principles, where the result is that the implementation of restitution of children can be submitted during the investigation stage and those who can submit are victims of children, parents or guardians of the victims themselves . Keywords ; restitution, children, victims, narcotics